The Effects of a Fluency Training Package on Paraprofessionals' Presentation of a Reading Intervention. (May 2013) - O'Keeffe, Breda V.; Slocum, Timothy A.; Magnusson, Renee
Paraprofessionals are widely employed in response to intervention (RTI) settings to provide instruction to students at-risk for reading disabilities. However, little research has addressed effective and efficient ways to train these paraprofessionals to deliver instruction with high fidelity. In addition, given the limited time and finances available in most districts, training needs to be as efficient as possible. This study assessed the effects of a 5-hour fluency training package on the presentation rates, praise rates, and error correction accuracy of five paraprofessionals providing supplemental reading instruction within an RTI system using a multiple baseline design across participants. Students' reading accuracy and percentage of intervals with on-task behavior were evaluated. Paraprofessionals generally increased their presentation rates, praise rates, and error correction accuracy. Students' behaviors were affected less.